ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI RENDAHNYA MOTIVASI BELAJAR SISWA MADRASAH ALIYAH NURUL IMAN: STUDI PENELITIAN KUALITATIF - Qodariyah, Niyar Ana; Prihandono, Trapsilo; Bektiarso, Singgih (Jurnal Inovasi Pendidikan dan Teknologi Informasi (JIPTI), 2024)
Motivation in the learning process is very important for students to have as a driving force for enthusiasm in learning. Low motivation in learning can have a negative impact on decreasing student interest and learning outcomes. this study aims to investigate the factors that contribute to low student learning motivation at Madrasah Aliyah Nurul Iman. The research method used is a qualitative approach by applying a single case study method. All students of Madrasah Aliyah Nurul Iman, totaling 73 students, became the research subjects. Data collection was conducted through direct observation, direct interviews, and documentation. The results revealed four main factors that influence students' low learning motivation. First, the inadequate condition of the school environment plays a role in reducing students' enthusiasm for learning. Second, students' lack of self-responsibility is also a factor that affects learning motivation. Third, parents' motivational support regarding the importance of education is insufficient, having a negative impact on students' enthusiasm for learning. Fourth, effective cooperation agreements between parents, school and pesantren in creating discipline for students also play a role. Thus, it can be concluded that there are four main factors that contribute to low student motivation at Madrasah Aliyah Nurul Iman.